Digital Marketing Communication Dalam Penghimpunan Zakat Di Indonesia - Zulfikri Zulfikri (Jurnal I-Philanthropy, 2022)
This study aims to analyze how it AISAS Model impacted the brand and image of OPZ when it publicised zakat. People's daily communication patterns, which formerly relied on a manual system but have now transitioned to a digital system, have changed as a result of the general rise of internet technology users. People can interact, exchange information, and communicate more easily because to technological advancements, which makes it simpler for them to make judgments. The amount of money raised for zakat since people began living more digitally orientated lives has increased by 30%. Zakat is still much below the intended level, according to data from Baznas, thus digital zakat management and introduction are required to reach a wider audience and raise the number of muzakki and improve zakat collections, respectively. According to Dentsu's theory in promoting and providing zakat literacy, starting with the audience's attention and then attracting (Interest) when displayed on social media and applications so that the audience searches (Search) receives all the information and decides in using the service (Action), all zakat management organizations (OPZ) that are not yet running optimally need to introduce zakat. This research utilizes a qualitative literature review methodology. The information used is secondary data, comprised of articles, books, publications, zakat-related material, and other publications. Secondary information reveals that Baznas has good zakat management, yet there are still OPZs that haven't done it.